The Influence of Teacher Ethics in Forming the Character of Primary School Students - Nazifah, Rahadatul; Khairat, Annisaul (Darul Yasin Al Sys, 2023)
Ethics involves principles, values, moral standards, and right and wrong actions in the context of human behavior. Ethics helps a person form moral views and understand contexts such as justice, right, wrong and responsibility. Teachers are role models for their students. The good and bad of the teacher's personality will influence the personality of the students. Because some students will imitate what they see, not what is said. Therefore, teachers must set good examples, both in the teaching process and outside. Because, a teacher's ethics greatly influence the character of his students. The purpose of this research is to determine the influence of teacher ethics in shaping student character. The method used in this research is a quantitative method, data obtained through distributing online questionnaires. The research results explain that teacher ethics plays a very important role in improving the character and quality of students, so that teachers can set good examples. The conclusion of this research explains that teacher ethics greatly influences the quality of students' character in the world of education and outside. The limitation of this research is that the researcher only conducted research on elementary school students so the data obtained was less relevant. The researcher hopes that future researchers can conduct research on middle school students. This research also recommends to future researchers that it be used as a benchmark in conducting research related to the influence of teacher ethics in shaping student character.